Genotoxicity testing for radon exposure: Dolichopoda (Orthoptera, Rhaphidophoridae) as potential bio-indicator of confined environments. Issue 2 (1st April 2014) - Gustavino, Bianca; Meschini, Roberta; Franzetti, Giulia; Gratton, Paolo; Allegrucci, Giuliana; Sbordoni, Valerio
Abstract: Radon represents the major source of natural radioactivity in confined environments. Despite the clear evidence of a direct association between residential exposure and human lung cancer provided by case-control studies, results relating indoor exposure and genotoxic/mutagenic effect induction are still contradictory. The present study attempts to estimate the genotoxic effects induced by exposure to radioactive radon in wild cricket populations sampled from caves where varying concentrations of radon are present. Cave crickets are also tested as possible bio-indicator organisms of genotoxic potential of contaminated residential and confined environments. Six caves in Central Italy are considered covering a broad spectrum of radon radioactivity concentration (221–26, 000 Bq/m 3 ). Dolichopoda specimens were sampled from each cave; both haemocytes and brain cells taken from individuals were tested for responsiveness to DNA damage induced by radon through the Comet assay. Specimens from the least radioactive cave, housed in controlled conditions for 60 days before analysis, were used as control group. Statistically significant increase of DNA damage was found in all groups of individuals from each cave, for both cell types. Very low values of all Comet parameters were found in control group individuals, which gave indications of a good responsiveness of the organism to the variable environmental levels of radioactive contamination. Results indicate that cave crickets represent a reliable tool for the detection of genotoxic potential induced by radioactive contamination of confined environments and can be proposed as a possible bio-indicator system for air (-radioactive) pollution related to indoor exposure.